Wayang Image Classification Using SVM Method and GLCM Feature Extraction - Muhathir Muhathir; M Hamdani Santoso; Diah Ayu Larasati (Universitas Medan Area, 2021)
Wayang is a masterpiece of art that has been able to survive centuries of change and development as a reflection of life for the majority of society. Wayang has a high value because it does not only function as a